2013
DOI: 10.1074/jbc.m112.436279
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Receptor TrkA, a New Receptor in Insulin Signaling Pathway in PC12 Cells

Abstract: Background: TrkA is a transmembrane receptor tyrosine kinase for nerve growth factor. Results: TrkA forms a molecular complex with insulin receptor and IRS-1 to induce Akt and Erk5 phosphorylation. Conclusion: The NGF-TrkA receptor influences insulin signaling. Significance: The TrkA receptor is involved in insulin signaling, and NGF may regulate neuronal glucose uptake as neurons are insulin-insensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In addition, we found differential expression of the InsR in PSNs innervating somatic and visceral organs, respectively. In PC12 cells, which share characteristics with nociceptive PSNs, the InsR has recently been shown to form a complex with TrkA, the receptor activated by NGF (Geetha et al 2013). NGF is essential in the development of functional traits and neurochemical phenotypes of nociceptive PSNs (Snider and McMahon 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found differential expression of the InsR in PSNs innervating somatic and visceral organs, respectively. In PC12 cells, which share characteristics with nociceptive PSNs, the InsR has recently been shown to form a complex with TrkA, the receptor activated by NGF (Geetha et al 2013). NGF is essential in the development of functional traits and neurochemical phenotypes of nociceptive PSNs (Snider and McMahon 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although, these studies suggested a crucial role of the InsR in neurite growth, it has also been demonstrated that the InsR forms a molecular complex with the TrkA in PC12 cells which show similarities with nociceptive sensory neurons [143]. Further, it has been demonstrated that TrkA is involved in insulin signaling by regulating the MAPK or Akt cascades [143].…”
Section: Role Of Insulin and Insrs In Neurite Outgrowth And Regeneratmentioning
confidence: 99%
“…In contrast, spontaneous regeneration was inhibited by local application of an anti-IGF antiserum to the injured nerve [152]. Recent findings suggest that the neurotrophic effects of insulin and IGF-1, similarly to NGF, may be mediated through activation of TrkA [143]. TrkA is also involved in the development of the neurochemical phenotypes of nociceptive PSNs and, importantly, the expression of the TRPV1 receptor is regulated by NGF [77,153].…”
Section: Role Of Insulin and Insrs In Neurite Outgrowth And Regeneratmentioning
confidence: 99%
“…[64][65] In comparison to other RTKs, TRK is most similar to the insulin receptor and has been implicated in insulin signaling. 67 Figure 1. Schematic view of TRK receptor tyrosine kinases and major signal transduction pathways involved in cell differentiation, proliferation, and survival.…”
Section: Trk Biology and Signalingmentioning
confidence: 99%